1995
DOI: 10.1021/bi00015a037
|View full text |Cite
|
Sign up to set email alerts
|

Key Disulfide Bonds in an Insect Hormone Binding Protein: cDNA Cloning of a Juvenile Hormone Binding Protein of Heliothis virescens and Ligand Binding by Native and Mutant Forms

Abstract: The hemolymph juvenile hormone binding protein (JHBP) from the early fifth instar larvae of Heliothis virescens (Lepidoptera, Noctuidae) has been purified, and three cDNA clones for this protein have been isolated from a fat body cDNA library constructed in bacteriophage lambda ZAP XR. The deduced amino acid sequence of the full-length clone predicts a mature protein consisting of 224 residues, a molecular mass of 24,976 Da, and a pI of 5.29. Comparison of the amino acid sequence to that of the previously desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 37 publications
2
53
0
Order By: Relevance
“…There is also no tryptophan residue in those proteins except only one residue in B. mori JHBP. The shift of Mr observed in G. mellonella MSP was also observed in JHBPs from SDS-PAGE (Touhara et al, 1993;Kurata et al, 1994;Wojtasek and Prestwich, 1995;Vermunt et al, 2001;Parkitna et al, 2002). Based on these facts, MSP of G. mellonella could be an outer member of the JHBP family.…”
Section: Archives Of Insect Biochemistry and Physiologysupporting
confidence: 53%
See 2 more Smart Citations
“…There is also no tryptophan residue in those proteins except only one residue in B. mori JHBP. The shift of Mr observed in G. mellonella MSP was also observed in JHBPs from SDS-PAGE (Touhara et al, 1993;Kurata et al, 1994;Wojtasek and Prestwich, 1995;Vermunt et al, 2001;Parkitna et al, 2002). Based on these facts, MSP of G. mellonella could be an outer member of the JHBP family.…”
Section: Archives Of Insect Biochemistry and Physiologysupporting
confidence: 53%
“…1987; Lerro and Prestwich, 1990;Wojtasek and Prestwich, 1995;Park and Kim, 1996;Vermunt et al, 2001;Parkitna et al, 2002). Four conserved cysteins found in JHBPs were also found in MSP.…”
Section: Archives Of Insect Biochemistry and Physiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Unfortunately, the complete amino acid sequence of the G. mellonellu JHBP is not known, but the known sequences of two other JHBP, from M. sexta and H. virescens hemolymph, show the presence of one potential glycosylation site, at Asn56 in M. sextu and Asnl9 in H. virescens JHBP (Wojtasek and Prestwich, 1995). Interestingly, the Asnl9 residue was not detected during sequencing of the Nterminal peptide of H. virescens JHBP by Edman degradation (Wojtasek and Prestwich, 1995), which suggests glycosylation of this residue. The authors did not comment on this result and did not consider the possibility of glycosylation of this residue, presumably because early studies on the closely related M. sexta JHBP did not indicate a detectable content of carbohydrates (Goodman et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The juvenile hormone-binding proteins from other insects, to which Takeout is related, are synthesized in the fat body and secreted into the hemolymph, where they are thought to carry juvenile hormone or other small lipophilic ligands to target cells (Nowock et al 1975;Glinka et al 1995;Wojtasek and Prestwich 1995). It is not known whether juvenile hormone plays any role in Drosophila male courtship behavior, but it has been shown that juvenile hormone stimulates the synthesis of accessory gland proteins (Herndon et al 1997).…”
Section: Genes and Development 2887mentioning
confidence: 99%